Strategic communication with reporting costs - Claude Fluet; Winand Emons (University of Bern, Department of Economics, 2016)
A decision-maker relies on information of parties affected by her decision. These parties try to influence her decision by selective disclosure of facts. As is well known from the literature, competition between the informed parties constrains their ability to manipulate information. We depart from this literature by introducing a cost to communicate. Our parties trade off their reporting cost against the effect on the decision. Typically, they never reveal all information. A better outcome may be implemented if the decision-maker adopts an active stance by barring one party from reporting or through cheap talk allowing coordination on a particular equilibrium.
Keywords: D82; K41; 330; disclosure; persuasion; active judging; adversarial; inquisitorial; Berichtswesen; Informationsverbreitung; Kosten; Theorie